Can utilization of the venous-to-arterial carbon dioxide difference improve patient outcomes in cardiogenic shock? A narrative review - Oskar Kjærgaard Hørsdal (American Heart Journal Plus)
Cardiogenic shock (CS) is a critical condition with high mortality, characterized by reduced cardiac output (CO) and tissue hypoperfusion, despite advancements in treatment. Traditional hemodynamic markers like CO measurements, monitoring of mixed venous oxygen saturation (SvO₂) and lactate levels have limitations, particularly in detecting microcirculatory dysfunction. The venous-to-arterial carbon dioxide tension difference (V-A PCO₂ gap, also known as P(V-A)CO2 and delta PCO2 or ∆PCO2) has been established as a sensitive marker of tissue perfusion and CO adequacy in septic shock but lacks extensive exploration in CS.This narrative review evaluates the possible uses of V-A PCO₂ gap in contemporary management of CS. Based on the available literature, it elucidates how the V-A PCO2 gap may offer valuable insight into tissue perfusion and CO adequacy in patients with CS. Elevated V-A PCO₂ gaps may reflect impaired clearance of CO₂ due to reduced CO and tissue hypoxia, serving as a reliable early indicator of circulatory failure. Integrating V-A PCO₂ gap monitoring into contemporary hemodynamic assessments holds potential to improve clinical decision-making, enabling more timely interventions and better stratification of patients at risk of deterioration.The sparse evidence suggests an association between elevated V-A PCO₂ gaps and poor outcomes in cardiac patients, including increased mortality and prolonged ventilation needs. Further research is needed to validate the use of this marker in CS and explore its potential to enhance treatment protocols by providing a more nuanced understanding of tissue-level perfusion, especially when macrocirculatory function appears normalized.